1985
DOI: 10.1016/s0735-1097(85)80279-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of sudden death after repair of tetralogy of fallot: Treatment of ventricular arrhythmias

Abstract: The majority of sudden deaths after repair of tetralogy of Fallot have been presumed to be due to ventricular arrhythmia; however, it remains to be demonstrated that antiarrhythmic medication reduces the incidence of sudden death. Since 1978, ventricular arrhythmias have been treated aggressively; these include any ventricular arrhythmia on routine electrocardiogram and more than 10 uniform premature ventricular complexes per hour on 24 hour electrocardiogram. A review was undertaken of 488 patients followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(43 citation statements)
references
References 18 publications
1
38
2
2
Order By: Relevance
“…Previous studies have shown that the clinically important arrhythmias are associated with older age at repair, 4,8,10,[12][13][14][15] large ventriculotomy, 10 high postoperative right ventricular pressure, 8,10,[12][13][14] tricuspid and/or pulmonary regurgitation, 2,12,15-17 cardiomegaly 2,18 or long QRS duration. 2,3,18 We therefore included these parameters in the data file for the analysis of risk factors.…”
Section: Subjectsmentioning
confidence: 99%
“…Previous studies have shown that the clinically important arrhythmias are associated with older age at repair, 4,8,10,[12][13][14][15] large ventriculotomy, 10 high postoperative right ventricular pressure, 8,10,[12][13][14] tricuspid and/or pulmonary regurgitation, 2,12,15-17 cardiomegaly 2,18 or long QRS duration. 2,3,18 We therefore included these parameters in the data file for the analysis of risk factors.…”
Section: Subjectsmentioning
confidence: 99%
“…A previous study revealed that RV systolic pressure more than 60 mmHg is a risk factor for ventricular arrhythmias and that residual RV to PA outflow gradient of more than 40 mmHg is a risk factor of SCD (19). However, other investigators suggest that the residual pressure load of RV is not a risk factor for SCD, and some studies have demonstrated that adequate RVOT obstruction might be advantageous against PR (20).…”
Section: Discussionmentioning
confidence: 99%
“…The cause of SCD can be surgical technical problems, ventricular dysrhythmias, aspiration and altered baroreceptor reflexes, and electrical instability resulting from postoperative anatomical modifications. Majority of SCDs after repair of tetralogy of Fallot were due to ventricular arrhythmia, which could be screened by routine electrocardiogram (ECG) in whom SCDs occur later, and successful antiarrhythmic treatment could effectively prevent from SCDs (15).…”
Section: Etiologiesmentioning
confidence: 99%